Dynamics of Anisotropically Supported Rotors - Agnes Muszynska; Charles T. Hatch; Donald E. Bently (International Journal of Rotating Machinery)
The paper discusses dynamic effects occurring in machinery rotors supported in bearings and pedestals with laterally different characteristics. In the considered rotor model the anisotropy of radial stiffness and tangential (“cross”) stiffness components are included. Within certain ranges of the rotative speed the support anisotropy leads to the specific, excited-by-unbalance rotor lateral synchronous vibrations in a form of backward (reverse) precession. In addition, one section of the rotor may precess backward, while the other section simultaneously precesses forward. Experimental results illustrate this phenomenon. The analytical model of the system is based on multimode modal approach. It is also shown in this paper that greatly enhanced information for machine malfunction diagnostics can be obtained by simulated rotation of the XY transducer system observing rotor lateral vibration. This simulated rotation can be accomplished by the machine diagnostic data acquistion and processing system. The data processing also includes extraction of forward and backward components of elliptical orbits filtered to one frequency, and the filtered orbit major axis magnitude and its angular orientation.